1981
DOI: 10.1002/1097-0142(19810515)47:10<2375::aid-cncr2820471009>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of nutritional assessment and support in cancer surgery

Abstract: Malnutrition is common in cancer patients and may be an important determinant of operative morbidity and mortality. To determine whether preoperative nutritional assessment can be used to identify a group of high-risk patients, and whether preoperative TPN decreases morbidity and mortality in this group, retrospective, nonrandomized review of 159 patients who were subjected to major cancer surgery was performed. All patients underwent preoperative multiparameter assessment. A previously developed and validated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
3

Year Published

1985
1985
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(55 citation statements)
references
References 15 publications
1
51
0
3
Order By: Relevance
“…Cancer patients with a PNI greater than 40% have been shown to have a significant decrease in postoperative morbidity and mortality if given preoperative total parenteral nutrition; no difference was noted in patients with a PNI below 40% [29]. The NI is based purely on laboratory parameters (IgM, prealbumin, complement C 3 , fibrinogen, cholesterol, retinol-binding protein, thyroxin-binding globulin); decreasing values indicate increased postoperative complication rates and mortality.…”
Section: Subjective Global Assessmentsupporting
confidence: 68%
See 1 more Smart Citation
“…Cancer patients with a PNI greater than 40% have been shown to have a significant decrease in postoperative morbidity and mortality if given preoperative total parenteral nutrition; no difference was noted in patients with a PNI below 40% [29]. The NI is based purely on laboratory parameters (IgM, prealbumin, complement C 3 , fibrinogen, cholesterol, retinol-binding protein, thyroxin-binding globulin); decreasing values indicate increased postoperative complication rates and mortality.…”
Section: Subjective Global Assessmentsupporting
confidence: 68%
“…Anthropometric responses to nutritional interventions are slow [29]. Measurements may be markedly affected by non-nutritional factors.…”
Section: Anthropometricsmentioning
confidence: 99%
“…Early studies suggested that aggressive nutritional therapy could improve the response to antineoplastic treatments or reduce the incidence and/or severity of complications in these patients [3,18]. However, later randomized controlled studies have suggested that aggressive nutritional therapy has no impact on tumor response, toxicity, or survival [1,9].…”
Section: Introductionmentioning
confidence: 99%
“…Malnourished patients are less likely than better nourished patients to tolerate surgery, radiation, and chemotherapy [1,32,41], and they often endure serious complications such as delayed wound healing, fistula formation, and infection. Malnourished patients also are hospitalized longer [26], and have a diminished quality of life [36] and lower survival rate than well-nourished patients [31].…”
Section: Introductionmentioning
confidence: 99%